22.7k views
4 votes
Does anyone know how to do this problem? If you can explain the steps as well it will be helpful. xx

Does anyone know how to do this problem? If you can explain the steps as well it will-example-1

1 Answer

4 votes
The relevant rules of exponents are

x^(a)\cdot x^(b)=x^((a+b))\\\\\left(x^(a)\right)^(b)=x^((a\cdot b))\\\\x^(-a)=(1)/(x^(a))

1.
(\left(8^(3)\right)^(4)\cdot 8^(-9))/(8^(3))=8^((3\cdot 4-9-3))=8^(0)=1

2.
(8^(3)\cdot 8^(4))/(\left(8^(2)\right)^(4))=8^((3+4-2\cdot 4))=8^(-1)
User Rohit Shelhalkar
by
5.8k points